Antioxidant Activities of 4-Methylumbelliferone Derivatives - Al-Majedy, Yasameen K.; Al-Amiery, Ahmed A.; Kadhum, Abdul Amir H.; Mohamad, Abu Bakar (PLOS ONE, 2016)
The synthesis of derivatives of 4-Methylumbelliferone (4-MUs), which are structurally interesting antioxidants, was performed in this study. The modification of 4-Methylumbelliferone (4-MU) by different reaction steps was performed to yield the target compounds, the 4-MUs. The 4-MUs were characterized by different spectroscopic techniques (Fourier transform infrared; FT-IR and Nuclear magnetic resonance; NMR) and micro-elemental analysis (CHNS). The in vitro antioxidant activity of the 4-MUs was evaluated in terms of their free radical scavenging activities against 2,2-diphenyl-1-picrylhydrazyl (DPPH), Nitric oxide radical scavenging activity assay, chelating activity and their (FRAP) ferric-reducing antioxidant power, which were compared with a standard antioxidant. Our results reveal that the 4-MUs exhibit excellent radical scavenging activities. The antioxidant mechanisms of the 4-MUs were also studied. Density Function Theory (DFT)-based quantum chemical studies were performed with the basis set at 3-21G. Molecular models of the synthesized compounds were studied to understand the antioxidant activity. The electron levels, namely HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital), for these synthesized antioxidants were also studied.